Revitalization of Agricultural Business Institutions to Increase the Socio-Economic Resilience of the Coastal Community of Baho Village - Erfain Erfain (Fakultas Teknologi Pertanian Unsultra, 2025)
Farmers’ institutional structures play a strategic role in strengthening the socio-economic resilience of coastal communities. Desa Baho, as one of the coastal villages, faces various challenges, including limited market access, insufficient capital, and inadequate knowledge of agricultural and fisheries technologies. This literature study aims to examine the role of revitalizing farmers’ institutions in improving the welfare of coastal communities. The method employed is a systematic literature review of journals, books, and research reports related to the strengthening of farmers’ institutions and coastal community empowerment from 2015 to 2025. The findings indicate that strengthening farmers’ institutions through the establishment of cooperatives, business management training, access to microfinance, and the use of appropriate technologies can increase productivity, income, and socio-economic capacity. Furthermore, strong institutions support collaboration among farmers, environmental risk mitigation, and adaptation to market changes. The discussion emphasizes the importance of an integrative strategy involving the government, academia, and the private sector to ensure the sustainability of farmers’ institutions. Institutional revitalization not only enhances economic capacity but also strengthens social networks, solidarity, and community participation in decision-making. In conclusion, revitalizing farmers’ institutions is an important instrument for strengthening the socio-economic resilience of coastal communities, and its implementation strategy must be tailored to local characteristics and the needs of the Desa Baho community.